x*x+4x-21=x+7

Simple and best practice solution for x*x+4x-21=x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*x+4x-21=x+7 equation:


Simplifying
x * x + 4x + -21 = x + 7

Multiply x * x
x2 + 4x + -21 = x + 7

Reorder the terms:
-21 + 4x + x2 = x + 7

Reorder the terms:
-21 + 4x + x2 = 7 + x

Solving
-21 + 4x + x2 = 7 + x

Solving for variable 'x'.

Reorder the terms:
-21 + -7 + 4x + -1x + x2 = 7 + x + -7 + -1x

Combine like terms: -21 + -7 = -28
-28 + 4x + -1x + x2 = 7 + x + -7 + -1x

Combine like terms: 4x + -1x = 3x
-28 + 3x + x2 = 7 + x + -7 + -1x

Reorder the terms:
-28 + 3x + x2 = 7 + -7 + x + -1x

Combine like terms: 7 + -7 = 0
-28 + 3x + x2 = 0 + x + -1x
-28 + 3x + x2 = x + -1x

Combine like terms: x + -1x = 0
-28 + 3x + x2 = 0

Factor a trinomial.
(-7 + -1x)(4 + -1x) = 0

Subproblem 1

Set the factor '(-7 + -1x)' equal to zero and attempt to solve: Simplifying -7 + -1x = 0 Solving -7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {-7, 4}

See similar equations:

| -6-6x=-42 | | 2(x-4)=65 | | 3x=65-3 | | 3s-10=36 | | -4+2(5x-6)=-3-39 | | -15=30x | | 12x^2+1x+5=0 | | -15=30 | | .4x+56=.6(x+80) | | 144+33=x | | 5q^2-10z=-12 | | -3(1+6m)=14-m | | x+12x=66 | | 6(6k+6)-5=1+6k | | x-15=30 | | -3+x=9 | | x(x+12)=66 | | .4x-5+.75=-.5x | | -x-8=23 | | 2x(x+4)-5x^2= | | x+12=66+x | | (.15x)=31.05 | | 8x-10x=20 | | 2x=66+12 | | -7x^2=-488 | | (.15x+x)=31.05 | | N-25=3-N | | 2(n+.3)=1.5+1+.5n-.3 | | (3x+12)-x=360 | | 666x^2=0 | | .6x+.1(100-x)=50 | | 2(a+3)=10 |

Equations solver categories